LITERASI KEUANGAN, FAKTOR DEMOGRAFI DAN AKSES PERMODALAN PENGARUHNYA TERHADAP KEPUTUSAN PENGAMBILAN KREDIT USAHA SEKTOR INFORMAL - darmawan, akhmad (Universitas Muhammadiyah Yogyakarta, 2019)
This study aims to anlyze effect of financial literacy, demographics factor (age, income, employment, education) and acces toward credit investment decision on informal sector business in West Purwokerto District. Sample in this study were 202 people taken by purposive sampling method. Data were analyzed using descriptive statistics test, validity test, reliability test, classical assumption test and multiple linear regression analysis. The results showed that financial literacy, employment, and access to capital have sign toward credit investment decision, education has an insignificantly positive effect toward credit investment decision. While both age and income have significantly negative effect toward credit investment decision.